"Frustrated with the whole system": a qualitative framework analysis of the issues faced by people accessing health services for chronic pain - Ria E. Hopkins; Louisa Degenhardt; Gabrielle Campbell; Sara Farnbach; Natasa Gisev (BMC, 2022)
Abstract Background Chronic non-cancer pain (CNCP) is complex and often requires multimodal management comprising of both pharmacological and non-pharmacological treatments. To inform delivery of CNCP management, it is important to understand how current health services providing non-pharmacological treatments are accessed by exploring the experiences of people attempting to access services. In doing so, this study sought to explore the underlying drivers of service access barriers. Methods This study explored the experiences of Australians accessing services for CNCP using semi-structured telephone interviews undertaken between 01 October 2020 and 31 March 2021. Thematic analysis was guided by Levesque et al.'s 2013 conceptual framework of access to health care, with emerging themes mapped to five dimensions of accessibility and corresponding abilities of consumers: Approachability/Ability to perceive; Acceptability/Ability to seek; Availability and Accommodation/Ability to reach; Affordability/Ability to pay; and Appropriateness/Ability to engage. Results The 26 participants (aged 24-78 years, 22 female) reported accessing a range of services including general practitioners (GP), allied health services, and specialised pain clinics, for a variety of conditions. Three themes were mapped to accessibility dimensions (in brackets): 'GP as guide or gatekeeper' (Approachability); 'Outside of my control' (Availability and Accommodation; Affordability); and 'Services aren't always good enough' (Appropriateness). A fourth identified theme illustrated how participants responded to encountering these barriers: 'Leading my own pain management'. Participant experiences suggest problems with the translation of contemporary pain management principles into practice, including continued application of biomedical health models as opposed to the biopsychosocial model, and demonstrate systemic issues with service delivery, including a lack of benchmarking of specialised services. Conclusions The identified themes highlight several evidence-to-practice gaps in the delivery of health services for people with CNCP in Australia. To address these gaps, there is a need for improved clinician training, increased investment in specialised pain services, and development of clear primary care pathways for CNCP management for evidence-based multimodal pain management to be accessible and equitable.